G05 Cognitive Impairment And Psychiatric Symptoms In A Danish Cohort Of Huntington's Disease Gene-expansion Carriers. (17th September 2014) - Vinther-Jensen, T; Unmack Larsen, I; Tolstrup Nielsen, T; Budtz-Jørgensen, E; Hjermind, LE; Nørremølle, A; Vogel, A; Nielsen, JE
Abstract : Background: Involuntary movements, neuropsychiatric symptoms, and cognitive impairment are all part of the symptom triad in Huntington's disease (HD). Despite the fact that neuropsychiatric symptoms and cognitive decline may be early manifestations of HD, the clinical diagnosis is conventionally based on the presence of involuntary movements and a positive genetic test for the HD CAG repeat expansion. Aim: To investigate the frequencies of the triad manifestations in a large outpatient clinical cohort of HD gene-expansion carriers. Methods: In this cross-sectional study, 107 Gene-expansion carriers from a Danish outpatient clinic were recruited. All participants underwent neurological examination, psychiatric evaluation and neuropsychological testing. Participants were categorised according to motor symptoms, neuropsychiatric symptoms, the use of psychotropic medication, and cognitive impairment. Results: Among the motor manifest HD gene-expansion carriers, 51.8% presented with the full symptom triad, 25.0% were defined as cognitively impaired, 14.3% had neuropsychiatric symptoms and only 8.9% had isolated motor symptoms. Among gene-expansion carriers without motor symptoms, 39.2% had neuropsychiatric symptoms, were cognitively impaired, or had a combination of the two. Conclusion: This is the first study to report the frequencies of motor symptoms, cognitive impairment, and neuropsychiatric symptoms in HD gene-expansion carriers in a national outpatient HD clinical cohort. We found that almost 40% of the gene-expansion carriers without motor symptoms had either neuropsychiatric symptoms, cognitive impairment or both, emphasising that these patients are not premanifest in psychiatric and cognitive terms, suggesting that the current clinical classification is neither necessarily suitable nor helpful for this patient group.